盲女古银霞的奇遇 ——黎紫书《流俗地》*: Gu Yinxia, A Blind Girl’s Adventure: Li Zishu’s Vulgar Land - Der-wei, David Wang (ERUDITE: Journal of Chinese Studies and Education, 2020)
《流俗地》代表黎紫書回歸寫實主義的嘗試，而寫實主義的傳統信條無他，就是以透視、全知的姿態觀看、銘刻人生百態。不論採取什麼視角，敘事者或作者理論上掌握訊息，調動文字，呈現聲情並茂的世界。《流俗地》對錫都人事栩栩如生的描寫，的確證明作者的寫實能量。 Vulgar Land embodies Li Zishu’s attempt to return to realism. The traditional creed of realism is nothing more than observing and engraving the vicissitudes of life through translucent, omnipotent expression. No matter what perspectiveshe takes, the narrator or the writer studies and grasps the information, deploying words and languages, presenting an eloquent world full of emotions. Vulgar Land’s vivid description of thelife and people in Xi Du (the tin town), has indeed proven the writer’s capable wield of realism. Keywords: Realism, Ruins of vision, feng tu, Sinophone Malaysian literature